Community Empowering through Tubers Crop Cultivation with its Compost Applications And Its Processing Technology - Warnita Warnita; Nalwida Rozen; Aisman Aisman (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2018)
Tuber crops (cassava and sweet potato) are potential sources of food that are widely used by the community. The demand for large quantities of potatoes increases every year. Therefore,we need to increase productivity. The purpose of this action research is to encourage student empathy to contribute and solve the problem in society by applying research results to improve the yield of tubers (cassava and sweet potato) through community service program which is named KKN-PPM. The methods applied by encouraging and motivating farmer groups, community leaders and small-processing industries. The activities are: 1) counseling, 2) training and 3) demonstration of compost application on sweet potato cultivation and cassava in farmer's land 4) manufacturing of various cassava processed products and 5) the application of packaging to products. The results of this KKN-PPM program are: 1) Increased awareness and empathy of students on economic, social and cultural issues so as to increase the income of the people; 2) The occurrence of partnerships between students who have various skills and technology so that can be realized a good cooperation to empower the community in cultivation of tubers and its processing; 3. increasing knowledge and technology among the cultivators and processors of tuber crops and packaging improvements so as to increase the selling price. 4. Positive response which is given by the community in the form of active participation and enthusiasm in following the activity from the beginning to end of the implementation.